An atmospheric approach to the city-psychosis nexus. Perspectives for researching embodied urban experiences of people diagnosed with schizophrenia - Marc Winz (Ambiances)
The aim of this paper is to ground an analysis of the city-psychosis nexus, and more precisely of the urban experience of individuals diagnosed with schizophrenia in a theoretical framework built on the notion of affective atmosphere, as conceptualized in recent Anglo-American human geography and on the notion of ambiance, as conceptualized in research on architecture and urban studies in France. Drawing upon the confrontation of those concepts, the paper highlights the similarities of ambiance and affective atmospheres, before underlining their differences. It is argued that an atmospheric approach points out dimensions not sufficiently taken into account in research in psychopathology. Furthermore, the two concepts stress two different registers of experience: whereas ambiance puts emphasis on a perceptual, sensory and conscious level of experience of urban environment, affective atmosphere highlights a more pre-reflective, bodily dimension. Finally, the paper sketches out a methodological framework in coherence with this conceptual distinction.